1996
DOI: 10.3171/jns.1996.85.4.0550
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of traumatic spondylolisthesis of the axis with nonrigid immobilization: a review of 64 cases

Abstract: Current treatment regimens for hangman's fracture, or traumatic spondylolisthesis of the axis, emphasize rigid immobilization using a halo orthosis. A retrospective study was undertaken to assess the safety and efficacy of nonrigid immobilization in the treatment of these fractures. Records of 64 patients with hangman's fracture treated over a 19-year period (1975-1994) at one institution were reviewed. Thirty-nine of these patients presented with a displacement of C-2 onto C-3 measuring less than 6 mm and no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
1
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 25 publications
3
69
1
11
Order By: Relevance
“…These injuries, characterized by minimally displaced fractures with a competent C2-C3 disc, are often effectively treated with a halo-vest orthosis or a hard cervical collar, with reported union rates approaching 100 % [38][39][40]. This is not unexpected, given the stability of the fracture in concert with a large surface area of apposed cancellous bone at the fracture site.…”
Section: Type I Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…These injuries, characterized by minimally displaced fractures with a competent C2-C3 disc, are often effectively treated with a halo-vest orthosis or a hard cervical collar, with reported union rates approaching 100 % [38][39][40]. This is not unexpected, given the stability of the fracture in concert with a large surface area of apposed cancellous bone at the fracture site.…”
Section: Type I Fracturesmentioning
confidence: 99%
“…There remains debate regarding the most appropriate immobilization technique, hard collar versus halo. Coric et al presented a consecutive series of 64 patients, all treated with Philadelphia collars and all achieving union [38]. While halovests are generally safe, they are associated with minor complications such as pin-site infections and avoidance of a halo may be best when possible.…”
Section: Type I Fracturesmentioning
confidence: 99%
“…Conservative treatment played a dominant role in the treatment of Hangman's fracture in the 1980s [1,7,15], and several researchers have reported a series of satisfactory cases using this technique. But some studies also have found disadvantages of conservative treatment, such as pseudarthrosis, anterior dislocation, angulation of C2 over C3, and recurrent axial pain [5,16]. In addition, long-term external immobilisation also produces much discomfort and inconvenience since the halo vest needs to be worn for a mean of three to six months [15,17].…”
Section: Discussionmentioning
confidence: 99%
“…Various surgical or nonsurgical treatments to achieve these aims have been described, but the optimal treatment remains in question. 2,9,23,24 Until quite recently, nonsurgical treatments were widely favored in the primary management of a hangman's fracture, even in the presence of instability.…”
mentioning
confidence: 99%
“…11 Studies have shown that anterior dislocation, angulation of C-2 over C-3, pseudarthrosis, and recurrent axial pain occur in about 60% of patients with Type II, IIa, and III fractures after conservative treatment. 2,9,23 The reported union rates following conservative management are 60% in Type II, 45% in Type IIa, and 35% in Type III hangman's fractures. 10 Vaccaro et al retrospectively investigated the early application of halo vest immobilization in a total of 31 hangman's fractures (27 Type II and 4 Type IIa).…”
mentioning
confidence: 99%